14-3-3ζ-A Novel Immunogen Promotes Inflammatory Cytokine Production - McGowan, Jenna; Peter, Cara; Chattopadhyay, Saurabh; Chakravarti, Ritu (Frontiers in Immunology, 2019)
The presence of autoantibodies against 14-3-3ζ in human autoimmune diseases indicates its antigenic function. However, neither the cause nor the consequence of this newly-identified antigenic function of 14-3-3ζ protein is known. To address this, we investigated the immunological functions of 14-3-3ζ by studying ex vivo effects on human peripheral blood mononuclear cells (PBMC) proliferation, polarization, and cytokine production. Exogenous 14-3-3ζ promoted PBMC proliferation and T cell polarization toward Th1 and Th17 populations. Significant increases in IFN-γ and IL-17 levels were observed in the presence of 14-3-3ζ. A specific increase in Th1 cells and IFN-γ production provided strong evidence for MHC class II presentation of 14-3-3ζ antigen. Particularly HLA-DRB1*0401 allele strongly promoted 14-3-3ζ-induced IFN-γ producing cells. In contrast, prednisolone treatment suppressed both 14-3-3ζ-induced T cell polarization and cytokine production. Overall, we show that MHC presentation and the adaptor functions of 14-3-3ζ participate in promoting IFN-γ and IL-17 production, two of the cytokines commonly associated with autoimmune diseases. To the best of our knowledge, this is the first report describing the ex vivo antigenic function of 14-3-3ζ with human PBMC, thereby providing the basis of its immunological role in human diseases.